2018
DOI: 10.3389/fpsyg.2018.00791
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Entrepreneurial Success: A Multilevel Study on Stakeholders of Micro-Enterprises

Abstract: The study provides an insight into the indicators and dimensions of entrepreneurial success as evaluated from the external stockholders’ perspective. As each firm is embedded in a network of relations with stakeholders (business partners), understanding how they evaluate entrepreneurial success is important. The initial qualitative study in the form of in-depth interviews allowed us to identify the indicators of entrepreneurial success that are identified by external stakeholders of micro-firms. In the quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 43 publications
(89 reference statements)
0
22
0
15
Order By: Relevance
“…Our five-factor structure of achieved success partially corresponds with six dimensions of entrepreneurial success as assessed by individual external stakeholders and identified by Razmus and Laguna (2018). These are entrepreneurs' satisfaction, work-life balance, firm social responsibility, firm reputation, satisfaction of employees, and clients' satisfaction.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our five-factor structure of achieved success partially corresponds with six dimensions of entrepreneurial success as assessed by individual external stakeholders and identified by Razmus and Laguna (2018). These are entrepreneurs' satisfaction, work-life balance, firm social responsibility, firm reputation, satisfaction of employees, and clients' satisfaction.…”
Section: Discussionmentioning
confidence: 94%
“…As suggested by Razmus and Laguna (2018), who found that there are different structures of success depending on the individual's vs. the firm-level external business partner's evaluations of success, it may be that achieved entrepreneurial success is not an isomorphic construct. Future research may wish to test the structural equivalence across different levels of analysis; for instance, at the firm level, research could aggregate views of employees and co-owners.…”
Section: Please Insert Figure 2 About Herementioning
confidence: 98%
“…Regarding the definitions of entrepreneurial success, the economic literature suggests that the financial performance of the firm is central; however, entrepreneurs themselves hold diverse views of success (Wach et al 2016). The definition of entrepreneurial success is inevitably connected with the way in which it is operationalized and approached in research (Razmus and Laguna 2018). As business performance may be different in different industry sectors and in different regional markets, researchers use two strategies to control for these differences.…”
Section: Entrepreneurial Successmentioning
confidence: 99%
“…The good condition of businesses and their successful functioning is of great societal importance, as entrepreneurial activity provides not only financial benefits and innovative solutions but also employment for a large part of the working population (Muller et al 2015;van Praag and Versloot 2007). It is therefore vital to gain insight into mechanisms related to entrepreneurial success-and it is not only economic but also psychological mechanisms that may play a prominent role here (Baron 2007;Rauch and Frese 2007;Razmus and Laguna 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Innovation is widely recognized as important for the effectiveness and success of organizations (Yuan and Woodman, 2010; Anderson et al., 2014; Razmus and Laguna, 2018). Due to the growing demands and expectations of customers and the global expansion of markets, innovation has become important for companies (Anderson et al., 2018).…”
Section: Introductionmentioning
confidence: 99%